ANALIYSIS OF GENERAL INSURANCE IN THE CURRENT PERIOD - Maria-Elena, Gheordunescu (Strategii Manageriale, 2013)
This paper aims to highlight the changes in the general insurance market in Romania in the past years. In the context of the financial and economic crisis, the Romanian insurance market recorded different siutations in recent years. It can be noticed that the growth rate slowed down compared with the level reached in 2007/2008. The main purpose of this paper is to present the insurance situation from the point of view of the relevant indicators for this insurance type. In the attempt of giving a convincing explanation, both theoretically and practically, I used in this paper as research methods: classification, synthesis and static and dynamic comparative analysis of the investigated events.